PERSEPSI GURU MATA PELAJARAN BAHASA INDONESIA DI SMP DAN MTS BOYOLALI TERHADAP PENILAIAN DALAM KURIKULUM 2013 - LISNAWATI, LISNAWATI (2016)
THE PERCEPTION OF INDONESIAN-SUBJECT TEACHERS IN SMP AND MTS BOYOLALI ON THE ASSESSMENT IN CURRICULUM 2013 ABSTRACT Lisnawati, Main Sufanti, Study Program of Indonesian Education, Teacher Training and Education Faculty, Muhammadiyah University of Surakarta. lisnawati91.lw@gmail.com This research aimed at: (1) explaining the perception of Indonesian-subject teachers on the kind of assessment in Curriculum 2013 in SMP (Junior High School), (2) presenting the strengths of assessment in Curriculum 2013 in SMP based on the teachers' perception, (3) presenting the weaknesses of assessment in Curriculum 2013 in SMP based on the teachers' perception. This research was a descriptive qualitative research with the research object was the perception of Indonesian-subject teachers on the assessment in Curriculum 2013. Data in this research were the teachers' opinions about the assessment of Curriculum 2013. The data sources were words said by the teachers when an interview was conducted or writings in every question provided by the researcher. The technique of data collection used the technique of interview and used the method of snowball sampling. Based on the results of the research, it was concluded that the teachers' perception about the kinds of assessment were: (1) assessment of behavior through observation, self-assessment, assessment among the students, and journal. (2) Assessment of knowledge through a written test, an oral test, and tasking. (3) Assessment of skill through a practical test, project, and portofolio. The strengths of assessment in Curriculum 2013 based on the teachers' perception were that it was more detailed, clearer, more complete, the students' data were more complete, and in the assessment of portofolio, the students' tasks could be covered more neatly in one task book. The weaknesses of the assessment in Curriculum 2013 based on the teachers' perception were that in the assessment of observation, the execution was longer and in the assessment of tasking, there was a possibility of cooperation among the students. Keywords: Perception, Indonesian-subject teachers, Curriculum 2013, and assessment.